Impact of Inflation, Markups and Wages on Changes in the Profitability of Enterprieses in Poland - Kosztowniak, Aneta (Journal of Finance and Financial Law, 2023)
The purpose of the study is to determine the impact of inflation, markups and wages on changes in the profitability of enterprises in Poland from 2008 to 2023, considering the effects in the short, medium and long term. Methodology refers to the impact of CPI, markups and wages on changes in gross turnover profitability rates (GTPR) that were assessed using the VECM model, the impulse response function, and the variance decomposition. Results of the research study show that the pillar of changes in the profitability of enterprises in Poland is its earlier changes with the increasing importance in the short term of markups, wages, and inflation (up to 10%) and gradually decreasing in the medium (up to 9%) and long term (7%). The importance of markups in the degree of explanation of changes in profitability is about 3–4 times stronger than that of wages. An increase in markups is an effective tool for stabilizing corporate profitability under inflation already in the short term, and can also be a tool to support an increase in such profitability in the medium and long term, if market conditions, including consumer demand, allow for it. The study fills a gap in the literature on the importance of markups and wages in shaping enterprises profitability in an inflationary condition, especially the use of markups as a tool that already produces expected effects in the short term.